ANALISIS PERAN DINAS KESEHATAN DALAM PENGAWASAN KUAITAS AIR MINUM ISI ULANG DI KOTA BANDA ACEH - Saiful Akbar (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
Clean drinking water is water that has passed the feasibility test according to applicable regulations. The preparation itself can be sourced from various types. Starting from water provided by the service, bottled drinking water, and what has recently emerged and become a cheaper alternative for drinking water is refilled drinking water. Refill drinking water cannot be separated from government supervision through the Health Service. The purpose of this study was to determine and examine the supervision of the Banda Aceh City Health Office on the quality of refill drinking water in Banda Aceh City and to identify and examine the inhibiting factors of the Banda Aceh City Health Office in monitoring the quality of refill drinking water in Banda Aceh City. Aceh. This study uses a descriptive qualitative approach. The analysis was carried out based on Syafie's supervisory theory which refers to functions in management to ensure that the work implementers run according to the standards set in the planning. According to Terry in Syafie said that supervision can be formulated as a process of determining what must be achieved, namely the standards that are being carried out, namely implementation, assessing implementation and if necessary making improvements so that implementation is in accordance with the plan, namely in line with standards (measures). The results of the study indicate that the government is obliged to always participate in individual businesses, are like refill drinking water managed by refill water depot entrepreneurs. The government can monitor refill drinking water depots that have met the health requirements through stickers that have been installed on the drinking water depots. For that the Health Department is required to supervise the quality of drinking water in every refilled drinking water managed by the community. Monitoring is carried out regularly so that the quality and quantity of drinking water at all depots is guaranteed, it was recorded that in 2020 out of 268 drinking water depots there were only 10 drinking water depots that received recommendations from the Health Office. Keywords: Supervision, Drinking Water Depot, Health Department